2012
DOI: 10.1186/1744-8069-8-27
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Minocycline on the Masticatory Movements following the Inferior Alveolar Nerve Transection in Freely Moving Rats

Abstract: BackgroundTo determine the effects of inferior alveolar nerve transection (IAN-X) on masticatory movements in freely moving rats and to test if microglial cells in the trigeminal principal sensory nucleus (prV) or motor nucleus (motV) may be involved in modulation of mastication, the effects of microglial cell inhibitor minocycline (MC) on masticatory jaw movements, microglia (Iba1) immunohistochemistry and the masticatory jaw movements and related masticatory muscle EMG activities were studied in IAN-X rats.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Recently, we examined whether glia are involved in the alteration of orofacial motor functions in NOP [ 118 , 119 , 120 ]. We demonstrated that injury to the infraorbital nerve, a sensory branch of the trigeminal nerve, alters masticatory performance in rats [ 118 , 119 , 120 ].…”
Section: Alteration Of Orofacial Motor Activity In Neuropathic Paimentioning
confidence: 99%
“…Recently, we examined whether glia are involved in the alteration of orofacial motor functions in NOP [ 118 , 119 , 120 ]. We demonstrated that injury to the infraorbital nerve, a sensory branch of the trigeminal nerve, alters masticatory performance in rats [ 118 , 119 , 120 ].…”
Section: Alteration Of Orofacial Motor Activity In Neuropathic Paimentioning
confidence: 99%
“…However, the effects of MAGL inhibitors on animal models of orofacial neuropathic pain have not been assessed. Injury to the trigeminal nerve in the orofacial area induced neuropathic pain in animal models (26)(27)(28)(29)(30). This type of nerve injury causes sensitization of the peripheral and central nervous systems (e.g., allodynia and hyperalgesia), which are typical characteristics of neuropathic pain (2,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a study, we observed that a selective MAGL inhibitor, JZL184, reduced NOP induced by injury to a branch of the trigeminal nerve in mice [258]. Trigeminal nerve injury was observed to induce neuropathic pain symptoms in the orofacial area [258,[263][264][265]. Systemic administration of the compound attenuated mechanical allodynia 2 h after administration [258].…”
Section: Route Of Administrationmentioning
confidence: 99%
“…Along with neurons, microglia may contribute to the synthesis and degradation of endocannabinoids [176,178,270]. Upregulated microglial cells in the brainstem trigeminal nuclei have been observed under NOP conditions to release pro-inflammatory mediators and contribute to the development of sensitization of brainstem neurons [113,179,263,264]. Activation of cannabinoid receptors in microglial cells by 2-AG may reduce the release of pro-inflammatory mediators.…”
Section: Route Of Administrationmentioning
confidence: 99%